2022
DOI: 10.1111/aje.13095
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating crop raiding by forest elephants and baboons at Kibale National Park

Abstract: In Africa, most protected forests are in densely human‐dominated landscapes where human–wildlife conflict is intense. We documented farmer perceptions and responses to crop‐raiding wildlife from Kibale National Park, Uganda. Crop raiding was mostly (95%) by baboons (Papio anubis) and elephants (Loxodonta africana). While the financial loss caused by baboons and elephants did not differ, elephants were perceived as more damaging. Guarding and trenches were perceived as the most effective deterrent strategies fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…In the arid Gonarezhou National Park (GNP) in Zimbabwe, forage quality is seasonal hence African savannah elephants roam the landscape guided by their own instinct in order to maximise on forage intake (Gandiwa et al, 2013). Consequently, African savannah elephants have migrated even outside protected habitats and raided crops leading to human-elephant conflicts (HEC) with proximal communities (Gandiwa et al, 2013;Kyokuhaire…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the arid Gonarezhou National Park (GNP) in Zimbabwe, forage quality is seasonal hence African savannah elephants roam the landscape guided by their own instinct in order to maximise on forage intake (Gandiwa et al, 2013). Consequently, African savannah elephants have migrated even outside protected habitats and raided crops leading to human-elephant conflicts (HEC) with proximal communities (Gandiwa et al, 2013;Kyokuhaire…”
Section: Introductionmentioning
confidence: 99%
“…Gandiwa et al., 2013; Ngene, 2010; Owen‐Smith & Chafota, 2012; Sievert et al., 2022; Wall, 2015) investigating African savannah elephant movement patterns and migration ecology in response to forage opportunities and poaching threats inside and outside protected areas indicated that their foraging behaviour threatened the resilience and stability of their habitat ranges. African savannah elephants, as true ecosystem engineers, shape their habitats in the process affecting their foraging opportunities (Jones et al., 1994; Kyokuhaire et al., 2023; Owen‐Smith & Chafota, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation